Kinetic Simulations of Radiative Magnetic Reconnection in the Coronae of Accreting Black Holes - Sironi, Lorenzo; Beloborodov, Andrei M. (The Astrophysical journal, 2020)
We perform 2D and 3D particle-in-cell simulations of reconnection in magnetically dominated e plasmas subject to strong Compton cooling. Magnetic reconnection under such conditions can operate in accretion disk coronae around black holes, which produce hard X-rays through Comptonization. Our simulations show that most of the plasma in the reconnection layer is kept cold by Compton losses and locked in magnetically dominated plasmoids with a small thermal pressure. Compton drag clears cavities inside plasmoids and also affects their bulk motions. These effects, however, weakly change the reconnection rate and the plasmoid size distribution from those in nonradiative reconnection. This demonstrates that the reconnection dynamics is governed by similar magnetic stresses in both cases and weakly affected by thermal pressure. We examine the energy distribution of particles energized by radiative reconnection and observe two distinct components: (1) A mildly relativistic peak, which results from bulk motions of cooled plasmoids. This component receives most of the dissipated reconnection power and dominates the output X-ray emission. The peak has a quasi-Maxwellian shape with an effective temperature of ∼100 keV. Thus, it mimics thermal Comptonization used previously to fit hard-state spectra of accreting black holes. (2) A high-energy tail, which receives ∼20% of the dissipated reconnection power. It is populated by particles accelerated impulsively at X-points or "picked up" by fast outflows from X-points. The high-energy particles immediately cool, and their inverse Compton emission explains the MeV spectral tail detected in the hard state of Cyg X-1. Our first-principle simulations support magnetic reconnection as a mechanism powering hard X-ray emission from magnetically dominated regions of accreting black holes.